In situ Protein Detection for Companion Diagnostics - Gremel, Gabriela; Grannas, Karin; Sutton, Lesley A.; Pontén, Fredrik; Zieba, Agata (Frontiers in Oncology, 2013)
The emergence of targeted therapies for cancer has created a need for the development of companion diagnostic tests. Assays developed in recent years are aimed at determining both the effectiveness and safety of specific drugs for a defined group of patients, thus, enabling the more efficient design of clinical trials and also supporting physicians when making treatment-related decisions. Immunohistochemistry is a widely accepted method for protein expression analyses in human tissues. Immunohistochemical assays, used to localize and quantitate relative protein expression levels within a morphological context, are frequently used as companion diagnostics during clinical trials and also following drug approval. Herein, we describe established immunochemistry-based methods and their application in routine diagnostics. We also explore the possibility of using immunohistochemistry to detect specific protein mutations in addition to DNA-based tests. Finally, we review alternative protein binders and proximity ligation assays and discuss their potential to facilitate the development of novel, targeted therapies against cancer.